Report on Gram Shikshan Mohim of Maharashtra - Planning Commission (Planning Commission, 1965)
Prof. V. K. R. V. Rao, Member (Education) desired that the various facets of the Gram Shikshan Mohim in Maharashtra may be studied by an on-the-spot survey of the work done in some villages and districts and through discussions with the officers and workers and various official and non- official organisations at the field level. Accordingly, I was asked to proceed to Maharashtra for this purpose and I stayed there from 8th April to 20th April, 1964. In this work, I was assisted by Shri J. C. Saxena, Research Officer, Education Division, Planning Commission and Shri K. B Rege, Instructor in Adult Literacy, National Fundamental Education Centre, New Delhi.
Government of India Planning Commission Education Division